The gospel of truth - 1,3:16.31 - 43.24 (TGOT) - Attridge, Harold W. (BrillOnline Reference Works, 2012)
The Gospel of Truth is written in the subachmimic dialect, characteristic of all the texts of Codex I with the exception of Pr. Paul and the dialect displays few of the irregularities encountered elsewhere, as in the Tri. Trac